Maternal Risk Factors for Preterm Birth in Murmansk County, Russia: A Registry‐Based Study. Issue 5 (26th May 2016) - Usynina, Anna A.; Postoev, Vitaly A.; Grjibovski, Andrej M.; Krettek, Alexandra; Nieboer, Evert; Odland, Jon Øyvind; Anda, Erik Eik
Abstract: Background: Globally, about 11% of all liveborn infants are preterm. To date, data on prevalence and risk factors of preterm birth (PTB) in Russia are limited. The aims of this study were to estimate the prevalence of PTB in Murmansk County, Northwestern Russia and to investigate associations between PTB and selected maternal factors using the Murmansk County Birth Registry. Methods: We conducted a registry‐based study of 52 806 births (2006–2011). In total, 51 156 births were included in the prevalence analysis, of which 3546 were PTBs. Odds ratios with 95% confidence intervals of moderate‐to‐late PTB, very PTB and extremely PTB for a range of maternal characteristics were estimated using multinomial logistic regression, adjusting for potential confounders. Results: The overall prevalence of PTB in Murmansk County was 6.9%. Unmarried status, prior PTBs, spontaneous and induced abortions were strongly associated with PTB at any gestational age. Maternal low educational level increased the risk of extremely and moderate‐to‐late PTB. Young (<18 years) or older (≥35 years) mothers, graduates of vocational schools, underweight, overweight/obese mothers, and smokers were at higher risk of moderate‐to‐late PTB. Secondary education, alcohol abuse, diabetes mellitus, or gestational diabetes were strongly associated with moderate‐to‐late and very PTB. Conclusions: The observed prevalence of PTB (6.9%) in Murmansk County, Russia was comparable with data on live PTB from European countries. Adverse prior pregnancy outcomes, maternal low educational level, unmarried status, alcohol abuse, and diabetes mellitus or gestational diabetes were the most common risk factors for PTB.